2022
DOI: 10.3390/fluids7080267
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Hydrological Models, HEC-HMS and SWAT in Runoff Estimation: Application to Huai Bang Sai Tropical Watershed, Thailand

Abstract: In the present study, the streamflow simulation capacities between the Soil and Water Assessment Tool (SWAT) and the Hydrologic Engineering Centre-Hydrologic Modelling System (HEC-HMS) were compared for the Huai Bang Sai (HBS) watershed in northeastern Thailand. During calibration (2007–2010) and validation (2011–2014), the SWAT model demonstrated a Coefficient of Determination (R2) and a Nash Sutcliffe Efficiency (NSE) of 0.83 and 0.82, and 0.78 and 0.77, respectively. During the same periods, the HEC-HMS mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Other studies represent that the HEC HMS model is quite reliable for simulating the magnitude and timing of peak flows, both during flood events and in long-term simulations [6,[12][13][14][15][16]. The HEC-HMS model produced a plausible compatibility between observed and simulated discharges on daily and monthly time scales [9] Both HEC-HMS and HBV were adequate for simulating river flow in tropical catchments with high humidity and limited data [17]. The HBV model simulation by Masitoh and Dasanto (2018) in the Upper Citarum watershed has quite good performance [18].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies represent that the HEC HMS model is quite reliable for simulating the magnitude and timing of peak flows, both during flood events and in long-term simulations [6,[12][13][14][15][16]. The HEC-HMS model produced a plausible compatibility between observed and simulated discharges on daily and monthly time scales [9] Both HEC-HMS and HBV were adequate for simulating river flow in tropical catchments with high humidity and limited data [17]. The HBV model simulation by Masitoh and Dasanto (2018) in the Upper Citarum watershed has quite good performance [18].…”
Section: Introductionmentioning
confidence: 89%
“…The HEC-HMS model packages various methods used in hydrological analysis. Several studies on the use of the HEC-HMS model show that the model was able to simulated low and medium flows accurately [9][10][11]. Other studies represent that the HEC HMS model is quite reliable for simulating the magnitude and timing of peak flows, both during flood events and in long-term simulations [6,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Calibration is the process of adjusting the model parameters to improve the agreement between the simulated results and observed data. In the present research, the Wainganga river basin was calibrated ) [6] (4)…”
Section: Model Calibrationmentioning
confidence: 99%
“…Many researchers with both model and observational data for modeled catchments have shown that HEC-HMS modeling yields very high performance. An example is the study by Chathuranika et al [45], who observed high efficiency between modeled and actual data. Moreover, according to Dukić and Erić [46], HEC-HMS modeling is suitable for uncontrolled catch- Despite the lack of daily observation data (an uncontrolled catchment), it can be expected that the modeled values of flow may consistent with reality.…”
Section: Modeling With Hec-hms Softwarementioning
confidence: 99%